A Conceptual Paper on Factors that Affect Intention of Gap Year - Yip, Foon Yee; Ah Chan, Ah Huai A. (INTI International University, 2018)
This is a conceptual paper to study the effects of factors on intention of taking gap year. The study reviews literature on four factors that play role on taking gap year. These factors are personal growth motivations, stress level, the student’s uncertainty regarding their future education plans, their parents’ attitudes regarding taking a gap year and the socioeconomic status of the student’s family. Studies and surveys related gap year were analyzed and discussed throughout the paper in the context of factors that influence gap year.